Polo-like kinase in trypanosomes: an odd member out of the Polo family - Kurasawa, Yasuhiro (Open Biol, 2020)
Polo-like kinases (Plks) are evolutionarily conserved serine/threonine protein kinases playing crucial roles during multiple stages of mitosis and cytokinesis in yeast and animals. Plks are characterized by a unique Polo-box domain, which plays regulatory roles in controlling Plk activation, interacting with substrates and targeting Plk to specific subcellular locations. Plk activity and protein abundance are subject to temporal and spatial control through transcription, phosphorylation and proteolysis. In the early branching protists, Plk orthologues are present in some taxa, such as kinetoplastids and Giardia, but are lost in apicomplexans, such as Plasmodium. Works from characterizing a Plk orthologue in Trypanosoma brucei, a kinetoplastid protozoan, discover its essential roles in regulating the inheritance of flagellum-associated cytoskeleton and the initiation of cytokinesis, but not any stage of mitosis. These studies reveal evolutionarily conserved and species-specific features in the control of Plk activation, substrate recognition and protein abundance, and suggest the divergence of Plk function and regulation for specialized needs in this flagellated unicellular eukaryote.